Refractory palatal hematoma due to intra-oral intake of Sunray surf clam Mactra chinensis: A case report - Kunio Yoshizawa; Akinori Moroi; Koichiro Ueki (Elsevier, 2022)
It is commonly the case that a slight degree of intra-oral hematoma results while eating, and this tends to heal spontaneously after several days. However, hard and incisive food can cause a refractory hematoma in the mouth. A 57-year-old Japanese woman consumed Sunray surf clam, known as Mactra Chinensis, for lunch and developed spontaneous pain in the mouth a few hours later, which resulted in a palatal hematoma. Refractory hematomas make it very difficult to differentiate between bleeding disease and neoplastic disease in a patient. A detailed history of etiology and thorough clinical examination are paramount to treatment. Although the patient in this case report was not affected by systemic illness, including bleeding diseases and neoplastic diseases, the patient required almost 2 weeks to recover from refractory palatal hematomas due to the intraoral intake of Sunray surf clam.